Disseminated Histoplasmosis in HIV-Patient in Nepal: A Case Report - Bastola, Anup; Pyakurel, Prajjwal; Maharjan, Kijan; Shrestha, Sanjay; Bastola, Rupak; Myneedu, Vithal Prasad; Paudel, Sunil; Devkota, Lina (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
The risk of disseminated Histoplasmosis increases among immunocompromised HIV infected patients. It can clinically present with skin manifestation. We report a forty years HIV infected male with severe immunodeficiency clinically presenting as a disseminated Histoplasmosis with dermatological manifestation and diagnosis.